Students’ Perspectives on Microteaching Impact on Their Performance In PLP II At The Sixth Semester Students of English Department of FKIP UKI Toraja - Viktor Siumarlata (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2021)
The objective of this research was to find out the students’ perspectives on Microteaching impact on their performance in PLP II program at the sixth semester students of English Education Study Program. This research used qualitative method. The informant of this research were students of English Education Study Program who had followed microteaching and PLP II Program. The writer used snowball sampling technique and stopped at 21 students to interview as informants, because the data were already saturared. The data of this research was collected by interview. The writer ued semi structure interview. The obtained data were analyzed in three major phase namely reduction, data display and conclussion. The resut of this research, is microteaching helped the students used expressions to opening and closing class, helped the students to manage time in learning process, boost their self-confidence, improved teaching skill, and as media to received upbuilding suggestions to expand their ability in teaching process. and also, microteaching as a media to apply the teaching comptence. Based on the result above, it can be concluded that microteaching helped the students of English Education Study Program of FKIP UKI Toraja, as mentioned abo